NOVEL, RESISTANT MICROALGAL POLYETHERS: AN IMPORTANT SINK OF ORGANIC CARBON IN THE MARINE ENVIRONMENT? - Gelin F.; Boogers I.; Noordeloos A.A.M.; Damste J.S.S.; Hatcher P.G.; De Leeuw J.W. (My University, 1996)
Five out of seven marine microalgal species investigated were found to biosynthesize nonhydrolysable, mainly aliphatic, biomacromolecules (algaenans). The molecular structure of the algaenan isolated from the microalga Nannochloropsis salina of the class Eustigmatophyceae was determined by solid state 13C NMR spectroscopy, Curie point pyrolysis - gas chromatography - mass spectrometry, and chemical degradations with HI and RuO4. The structure is predominantly composed of C28--C34 linear chains linked by ether bridges. The algaenan isolated from a second eustigmatophyte (Nannochloropsis sp.) was structurally similar. Algaenans isolated from two chlorophytes also possess a strongly aliphatic nature, as revealed by the dominance of alkenes/alkanes in their pyrolysates. Accordingly, we propose that the aliphatic character of numerous Recent and ancient marine kerogens reflects selectively preserved algaenans and that these algaenans may act as a source of n-alkanes in marine crude oils.